Assessing the faecal source sensitivity and specificity of ruminant and human genetic microbial source tracking markers in the central Ethiopian highlands. (24th December 2020) - Linke, R.B.; Kebede, G.; Mushi, D.; Lakew, A.; Hayes, D.S.; Graf, W.; Farnleitner, A.H.
Abstract: This study tested genetic microbial source tracking (MST) methods for identifying ruminant‐ (BacR) and human‐associated (HF183/BacR287, BacHum) bacterial faecal contaminants in Ethiopia in a newly created regional faecal sample bank ( n  = 173). BacR performed well, and its marker abundance was high (100% sensitivity (Sens), 95% specificity (Spec), median log10 8·1 marker equivalents (ME) g −1 ruminant faeces). Human‐associated markers tested were less abundant in individual human samples (median: log10 5·4 and 4·2 (ME + 1) g −1 ) and were not continuously detected (81% Sens, 91% Spec for BacHum; 77% Sens, 91% Spec for HF183/BacR287). Furthermore, the pig‐associated Pig2Bac assay was included and performed excellent (100% Sens, 100% Spec). To evaluate the presence of MST targets in the soil microbiome, representative soil samples were tested during a whole seasonal cycle ( n  = 60). Only BacR could be detected, but was limited to the dry season and to sites of higher anthropogenic influence (log10 3·0 to 4·9 (ME + 1) g −1 soil). In conclusion, the large differences in marker abundances between target and non‐target faecal samples (median distances between distributions ≥log10 3 to ≥log10 7) and their absence in pristine soil indicate that all tested assays are suitable candidates for diverse MST applications in the Ethiopian area. Abstract : Significance and Impact of the Study: Faecal water pollution poses a health risk to its users worldwide, especially in developing countries where safe household water supplies and sanitary facilities are often scarce or non‐existent. This study tested for the first‐time genetic microbial source tracking (MST) methods for identifying ruminant‐ and human‐associated bacterial faecal contaminants in Ethiopia in an extensive regional faecal sample bank. The results indicated the marker's suitability for diverse MST applications in the Ethiopian area. Their application will aid policy makers to make proper risk assessment, take corrective action in the management of surface waters and the implementation of remediation measures supporting public health.